Cognitive decline : strategies for prevention - Fillit, Howard; Butler, Robert N., 1927-2010 (Greenwich Medical Media : Distributed by Oxford University Press, 1997)
Cognitive Decline - Strategies for Prevention examines the problems associated with our understanding of the aging brain, whether or not such decline is inevitable and if there are practical steps which can be taken to prevent or minimise cognitive decline in late life. Our knowledge about the prevention of cognitive decline and dementia in old age has grown rapidly in recent years and it is becoming clear that preventive strategies are now viable.